Estratégia política e gestão territorial - Lubambo, Cátia; Jucá, Antônio (Ciência & Trópico, 2013)
RESUMO O texto apresenta discussão sobre a gestão do território na perspectiva de uma avaliação das condições que formam o ambiente político-institucional nos municípios e das estratégias institucionais, sob a dimensão da intersetorialidade governamental e da coordenação entre esferas de governo. São analisadas, comparativamente, quatro experiências municipais no âmbito da gestão territorial; duas no Estado de Pernambuco: Águas Belas e Paranatama e duas no Estado de Santa Catarina: Cerro Negro e Campo Belo do Sul. Chama-se atenção para a competitividade política local aliada à ausência de capacidade institucional, nos governos subnacionais, como fatores limitantes ao sucesso das experiências de ação pública descentralizada. Há uma referência analítica a outros estudos que focalizam fóruns regionais de programas territoriais e que têm sinalizado resultados nesta direção, seja no âmbito dos ministérios ou dos Governos Estaduais. A análise traz reflexões sobre como fatores político-institucionais podem ser favoráveis à atuação de fóruns participativos e sugere uma abordagem em que se considerem os atores políticos locais na definição do território, em contraposição às concepções formadas a partir de critérios apenas programáticos. PALAVRAS-CHAVE: Território. Governança. Representação Política. STRATEGY AND TERRITORIAL MANAGEMENT ABSTRACT The analysis highlights local political competition associated with lack of institutional capacity of local of sub-national governments (state and municipal) as key factors which limit the accomplishment of these decentralized public actions. The analysis refers yet to other studies that focus regional forums of land programs, both from state or federal government initiative, and they arrive to similar conclusions. This paper presents the debate on landscape management, focusing the assessment of the conditions which constitute the political and institutional environment in local or municipal governments. In this context, the institutional strategies concerned are approached both as involving the inter-sectors policies dimension, as well as the areas responsible for these issues in all level of governments. Thus, the analyses compare five municipal experiences in the scope of land management, two of them in the State of Pernambuco (namely in Àguas Belas and Paranatama), two others in the State of Santa Catarina (in Cerro Negro and Campo Belo do Sul) and one in the State of Goiás (in Goiania). In summa, this paper reveals how political and institutional factors can be favorable to the role of participatory assemblies and suggests a research approach which encompasses local political actors in the definition of the territorial scene, in oppose to analyses and evaluations concepts which just consider political programs as criteria for performance. KEYWORDS: Territory. Governance. Public Representation.